Three new species of Empoasca (Hemiptera: Cicadellidae: Typhlocybinae: Empoascini) from northern South America - Southern, Phillip Sterling (Zootaxa, 2006)
Three new species of the leafhopper genus Empoasca are described and illustrated from Ecuador and Colombia. The species are placed in a previously published key and relationships to other species of the genus are discussed.